Aspect of Early Aesthetical Development in the Pedagogical Systems of F. Fröbel and M.Montessori - Ragozina, Viltor (Pedagogical Discourse, 2013)
Conceptual approaches and technologies of foreign teachers are considered in the context of aesthetic development of child of early age. The comparative analysis of pedagogical principles and features of didactic methods of Fröbel and Montessori is produced with an accent on education of perceptible sphere of child, necessity of the early beginning of teaching, on basis of which of emotions and senses are formed, education in preschool establishments and distinctions and distinctions which consist in creation of the special materials for teaching and author methods and by their realization in the different types of preschool establishments – child’s gardens of Fröbel and houses of child of Montessori.